Answer:
x = 1/3 or 0.333333
Step-by-step explanation:
Simplify to the left side.
Simplify each term.
Multiply 3 by -2
-6 + 6 (x + 1) -2 = 0
Apply the distributive property.
-6 + 6x + 6 * 1 - 2 = 0
Multiply 6 by 1.
-6 + 6x + 6 - 2 = 0
Simplify the expression.
Add -6 and 6.
6x + 0 - 2 = 0
Add 6x and 0.
6x - 2 = 0
Add 2 to both sides of the equation.
6x = 2
Divide each term by 6 and simplify.
Divide each term in 6x - 2 by 6.
(6x) / 6 = 2 / 6
Reduce the expression by canceling the common factors.
x = 2/6
Reduce the expression by canceling the common factors.
x = (2(1)) / 6
Cancel the common factors.
x = (2 * 1) / (2 * 3)
The result can be shown in multiple forms.
Exact form:
x = 1/3
x = 0.33333333